Identity change of the disable body during 1st half of the 20th century: On the Roads of Misery. Memories from the Battles for Independence and the Life of the Blind by Pranas Daunys - Birgerytė, Aistė (Literatūra, 2015)
The article introduces the first autobiography of the disabled in the 20th century Lithuanian literature – the memoirs of Pranas Daunys – On the Roads of Misery / Memories from the Battles for Independence and the Life of the Blind. In the context of the disability body studies, the article discusses different levels in the formation of the corporal identity of the blind person. The study emphasizes the importance of cultural space to the identity of the blind, which is related to the Braille. The article explains the integrity dimension of the blind person’s identity, which mergers different experiences of personal life (the experience of eye trauma during the war and the memories of patriotic feelings), which are equally important to the personal identity. The research deals with the corporal and sensual self-perception of the blind, which is closely related to the social and public emancipation, changing the lines of national identity.